Decision-making, motivation and life inspirations of the potential tagasalo - Artuz, Raje Paul; Revesencio, Nina I. (2009.)
The study sought to identify, determine and describe the distinct decision-making orientations of the potential Tagasalo, the motivation that influences their dispositions, and their life aspirations. Results shows that potential Tagasalos have relied most of their decisions on their families' current economic state. Also, personal decisions were still anchored on family followed by their will and choice respectively. More so, most of the participants were intrinsically motivated and affected by family roles and values, which in turn influence their life aspirations. Findings show that indeed, aspirations of potential Tagasalos were intrinsic in nature and viewed to be more attainable compared to that of extrinsic aspirations.
Thesis (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Tagasalos